2019
DOI: 10.1097/inf.0000000000002227
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Full-dose, Split-virion, Inactivated, Quadrivalent Influenza Vaccine in Healthy Children 6-35 Months of Age

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Vaccines more similar to currently available split-virus inactivated products have demonstrated less reactogenicity ( 34 ). Since November 2016, three IIV4s (Fluarix Quadrivalent, FluLaval Quadrivalent, and Fluzone Quadrivalent) have been approved for administration to this age group at the higher 0.5-mL dose (containing 15 µ g of HA per vaccine virus) on the basis of studies demonstrating acceptable safety profiles ( 35 37 ).…”
Section: Recommendations For the Use Of Influenza Vaccines 2019–20mentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccines more similar to currently available split-virus inactivated products have demonstrated less reactogenicity ( 34 ). Since November 2016, three IIV4s (Fluarix Quadrivalent, FluLaval Quadrivalent, and Fluzone Quadrivalent) have been approved for administration to this age group at the higher 0.5-mL dose (containing 15 µ g of HA per vaccine virus) on the basis of studies demonstrating acceptable safety profiles ( 35 37 ).…”
Section: Recommendations For the Use Of Influenza Vaccines 2019–20mentioning
confidence: 99%
“…Licensure of the 0.5-mL dose volume for this age group was based on a randomized, observer-blinded, multicenter safety and immunogenicity study conducted among 1,950 children aged 6 through 35 months, who were randomized 1:1 to receive either 0.25 mL or 0.5 mL of Fluzone Quadrivalent ( 37 , 108 ). In the safety analysis, the overall safety profile was similar between the two groups.…”
Section: Influenza Vaccine Composition and Available Productsmentioning
confidence: 99%
“…In the first trial, full dose Fluzone had a similar safety profile to half-dose Fluzone with a single adverse event being attributed to the study vaccine. 13 Similarly, the second study found that full-dose Flulaval may improve protection against influenza in some young children when compared to low-dose Fluzone, and in this trial none of the adverse events were considered to be study-related by the investigator. 11 The final trial evaluated Vaxigrip Tetra (15μg/strain) administered to children and adolescents in two different formats.…”
Section: Resultsmentioning
confidence: 87%
“…Four of the included studies evaluated quadrivalent influenza vaccines (QIV) in children. 5, 11-13 All of the studies reported reactogenicity outcomes and adverse events. One study reported both TIV and QIV vaccines and the results are reported above.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have generally shown comparable reactogenicity and non-inferior immunogenicity with the full dose, in comparison with the half dose, in children 6-35 months of age [22][23][24][25]. Statistically superior immunogenicity was seen only in infants between 6-11 months of age, for H3N2 and B/Yamagata and not for H1N1 [25].…”
Section: Uniform Dosing For Inactivated Influenza Vaccinesmentioning
confidence: 97%